Piotr Skarga w publicystyce rokoszu Zebrzydowskiego - Baczewski, Sławomir (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The attitude of Piotr Skarga toward occurrences from the years 1606–1609 was defined by his political opinions, which bases were monarchism and Catholicism of the Counter Reformation. In the discussed time Skarga voiced his opinions in three works. His invectives had a little in common with the truth. The main invective regarding the “rebels” concerned the crime against the Roman Catholic Church. The remaining matters were only an addendum of the main issue. Meanwhile, for the “rebels” more important than confession were nobility and citizenship. Hence came Skarga’s entire incomprehension for demands and system of nobles. There were many more writings which appeared as impostors of Piotr Skarga. The authors, for the most part anonymous, described thepreacher as the supreme enemy, the sower of discord, the destroyer of freedom and the embodiment of evil. T hey alleged him a peasantorigins, hypocrisy, and false care for the country. Skarga was the enemy of the political nation of The Polish-Lithuanian Commonwealth, hated all of that nation matters. Still, the Polish people from XIXth and XXth centuries committed to memory the adherents of Zebrzydowski as the “rebels”, even if “rebels” really basically understood, what was the reason of The State of the Polish-Lithuanian Commonwealth.